Caesalpinia sappan L: REVIEW ARTICLE - Vardhani, Afifah K (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Caesalpinia sappan L, synonym Biancaea sappan L., is a medicinal plant used in Asia, especially India, China, and Southeast Asia. In Indonesia, Sappanwood (Secang) is traditionally consumed as herbal drink to boost immune system, kill bacteria, treat diarrhea, and tumor. Caesalpinia sappan L. contains homoisoflavonoids and phenols such as brazilin, brazilein, and other active ingredients. Aim: The aim of this study is to report phytochemical contents and benefits of Caesalpinia sappan L for medicinal use.Methods: The method used in finding articles was a literature review, using the keywords. Search was conducted electronically using several databases, including Science Direct and Google Scholar.Results: Medicinal benefits from Caesalpinia sappan L have been proved by several studies. These medicinal effects are caused by the presence of Caesalpinia sappan?s active ingredients such as brazilin, brazilein, 3-deoxysappanchalcone, sappanchalcone, Caesalsappanins A, G, H, and I.Conclusion: Caesalpinia sappan L has medicinal benefits and could be applied to treat several diseases.